2006
DOI: 10.1002/adfm.200500767
|View full text |Cite
|
Sign up to set email alerts
|

Stable and Efficient White Electroluminescent Devices Based on a Single Emitting Layer of Polymer Blends

Abstract: An efficient orange‐light‐emitting polymer (PFTO‐BSeD5) has been developed through the incorporation of low‐bandgap benzoselenadiazole (BSeD) moieties into the backbone of a blue‐light‐emitting polyfluorene copolymer (PFTO poly{[9,9‐bis(4‐(5‐(4‐tert‐butylphenyl)‐[1,3,4]‐oxadiazol‐2‐yl)phenyl)‐9′,9′‐di‐n‐octyl‐[2,2′]‐bifluoren‐7,7′‐diyl]‐stat‐[9,9‐bis(4‐(N,N‐di(4‐n‐butylphenyl)amino)phenyl)‐9′,9′‐di‐n‐octyl‐[2,2′]‐bifluoren‐7,7′‐diyl]}) that contains hole‐transporting triphenylamine and electron‐transporting ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
54
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(59 citation statements)
references
References 39 publications
5
54
0
Order By: Relevance
“…Therefore, it is reasonable to expect that a dendrimer with PCs of both hole and electron (bipolar) transport properties could further facilitate charge injection and transport and improve device performance. A good way to produce a bipolar transporting material is to introduce both donor and acceptor components in a single molecule, a technique which has been frequently utilized to make bipolar small-molecular emitters [25,26] and host materials [27]. However, the number of donor-acceptor dendrimers with surface-tocore energy transfer is rather limited [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is reasonable to expect that a dendrimer with PCs of both hole and electron (bipolar) transport properties could further facilitate charge injection and transport and improve device performance. A good way to produce a bipolar transporting material is to introduce both donor and acceptor components in a single molecule, a technique which has been frequently utilized to make bipolar small-molecular emitters [25,26] and host materials [27]. However, the number of donor-acceptor dendrimers with surface-tocore energy transfer is rather limited [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] These properties could be very important for example when trying to achieve white emission, one of the most important developments in the field of polymer emitting devices, where complex mixtures are used in order to gain broad white emission and balanced electron and hole transport within a single "emission" layer. [8,9,10,11] Polyfluorenes have been extensively studied for display applications, owing to their pure blue and efficient electroluminescence coupled with a high charge carrier mobility and good processability. [12] Several studies have been reported, including mixing of polyfluorenes with different emissive materials and applying them in single or multiple layers.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous reports have demonstrated that utilizing the blending techniques, single-layer polymer light-emitting device ͑PLED͒ with high performance can be achieved. [1][2][3][4][5] Both the carrier injection and transport can be improved by carefully selecting the materials and their proportions in the blend. [1][2][3][4][5] Furthermore, the dopant introduction produces a dilution effect of the polymer solution and reduces polymer interchain interaction, leading to sharper EL spectra with higher color purity than those of the neat polymer film, depending on the dopant concentration.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] Both the carrier injection and transport can be improved by carefully selecting the materials and their proportions in the blend. [1][2][3][4][5] Furthermore, the dopant introduction produces a dilution effect of the polymer solution and reduces polymer interchain interaction, leading to sharper EL spectra with higher color purity than those of the neat polymer film, depending on the dopant concentration. [5][6][7] In conjugated polymers, intrachain singlet excitons can be generated by photons absorption or via carrier-injection followed by electron-hole pair formation on a single chain.…”
mentioning
confidence: 99%